Assessment of land degradation in Guizhou Province, Southwest China using AVHRR/NDVI and MODIS/NDVI data - Qiuhao Huang; Manchun Li; Chong Chen; Kun Mao; Zhenjie Chen; Feixue Li; Dong Chen (2010 18th International Conference on Geoinformatics, 2010)
Monitoring and assessing land degradation is important to local sustainable development in Guizhou province, Southwest China, where limestone distributed about 61.7 %. Using the 1 km Advanced Very High Resolution Radiometer Normalized Difference Vegetation Index (AVHRR/NDVI) data (1992-1993) and 500 m, Moderate Resolution Imaging Spectroradiometer Normalized Difference Vegetation Index (MODIS/NDVI) (2002-2003) in growing seasons (AprilSeptember), this paper assessed land degradation in Guizhou Province, Southwest China from 1992 to 2003. Comparison of NDVI change in limestone-distributed area and non-limestone distributed area in 7 biophysical geography zones were also performed. The final result shows the spatial pattern of land degradation during the past 10 years and suggests that lime-distributed areas are easily degraded than non-limestone distributed areas. All these finding may serve as a strong basis for decision making in regard to land resource management and environmental rehabilitation.